Adamantinomatous craniopharyngioma mistaken as rathke cleft cyst: a case report - Haroon, Raihanah; Mustfar, Siti Nor Suzeana; Abu Bakar, Intan Bazilah; Che Mohamed, Siti Kamariah; Hassan, Radhiana (2021)
ADAMANTINOMATOUS CRANIOPHARYNGIOMA MISTAKEN AS RATHKE CLEFT CYST: A CASE REPORT Raihanah Haroon*1 ; Siti Nor Suzeana Mustfar1 ; Intan Bazilah Abu Bakar1 ; Radhiana Hassan1 ; Siti Kamariah Che Mohamed1 1Radiology Department, IIUM, International Islamic University of Malaysia INTRODUCTION: A great variety of lesions can be found in the suprasellar region, often with similar clinical presentations; posing difficulty while investigating it. When a suprasellar mass is encountered, the differential diagnosis is crucial in order for the operating surgeon to determine further management including the surgical approach as well as the degree of resection. However it is not always easy if the mass exhibits mixed solid cystic or entirely cystic features. REPORT: The author presents a case of a 19-year-old lady who initially presented with left facial weakness, subsequently has been followed up several years for Rathke’s cleft cyst (RCC) in view of its MR appearance. But recently the patient complained of eye symptoms, occipital headache and amenorrhea. Repeat MRI showed increasing size of the suprasellar mass and local mass effect unto the optic chiasm. Patient underwent deroofing of the cyst with the histopathological examination which revealed adamantinomatous craniopharyngioma, WHO grade 1. Nevertheless, possible transformation of RCC into craniopharyngioma is not known in view of no tissue diagnosis obtained earlier on. Review of MR appearances of these two entities in previous literature as well as the radiopathological correlation and differentiating features are presented. CONCLUSION: Though the imaging features are characteristic for both entities, radiologists should be aware of the possible atypical appearance mimicking each other. Postulated hypothesis that both lesions arise from the same spectrum of cystic ectodermal lesions of the sellar region as well as possible transformation of RCC into craniopharyngioma also needs to be considered.